A extensão do vocabulário receptivo e sua relação com a compreensão da leitura em crianças brasileiras do 1º ao 5º ano do Ensino Fundamental - Matos, Lilian Meibach Brandoles de (2018)
The domain of language is one of the fundamental elements for social life and fundamental in thought processes. The oral language can be receptive and expressive: the receptive refers to the individual's ability to understand what he hears, that is, to understand oral language; the expressive represents the individual's ability to speak and communicate orally. The present study has the main objective to identify the extension of the receptive vocabulary of a group of Brazilian children of elementary school and its relation with the reading comprehension. For this it was necessary: to verify the extension of the receptive vocabulary of students from 1st to 5th year; check reading comprehension; to investigate the relationship between the extension of the receptive vocabulary and the reading comprehension; to verify how the variable age behaves in the receptive vocabulary analyzes, the reading comprehension and the relation between them. The sample came from a private school that serves children from families of high socioeconomic status in the city of São Paulo. 95 students participated from the 1st to 5th year of elementary school. Two instruments were used: Peabody Image Receptive Vocabulary Peabody Test and Reading and Sentence Comprehension Test (TELCS). The results obtained in this study were expressed as mean and standard deviation for each age group, school year, receptive vocabulary and reading comprehension test. An analysis of variance (ANOVA) was conducted and Tukey's post hoc test was also used. The evaluation of the receptive vocabulary with the Peabody test allowed us to conclude that there is a significant difference in Peabody performance according to age and school year. The results indicated that the children had a growing extension of the receptive vocabulary and level of reading comprehension, according to the increase of age and schooling. It was possible to observe a significant correlation between the extension of the receptive vocabulary and the level of reading comprehension of the 3rd, 4th, and 5th grade students